E-Culture as a Source for Learning History and Culture for Students of the History Education Department Mulawarman University, Samarinda - Norhidayat Norhidayat (JURNAL HISTORICA, 2023)
In today's modern era all learning refers to digital-based things, both in terms of sources and media as well. It is also inseparable from learning in schools and tertiary institutions, in practice using digital-based media in accordance with current technological developments. The study, entitled E-Culture as a Source for Learning History and Culture for the Cultural History Course for Students of the Unmul History Education Department, uses a qualitative research method with data obtained from observations, questionnaires and interviews. E-culture is one of the applications available on digital platforms and can be used as a instructional media for students of history and culture. It is also inseparable from students of the Teacher Training and Education Faculty of history education Department at Mulawarman University. They use this application as a learning medium in history and culture courses. In its use, e-culture tends to contain the history and local culture of the people of Kalimantan, the focus is on the Dayak community as the largest tribe in Kalimantan. Students can take advantage of this application to increase their knowledge and be relevant to existing courses. Access to the application is also very easy and free, so students can make the most of it. Like applications that are developing today, e-culture also has drawbacks and is always developing in updates related to data and information. The advantage is that apart from being easy to use as a learning medium, there are also interactive tools that receive input and suggestions from users in terms of updating the latest information and data. Keywords: e-culture, learning history, history education, mulawarman university